Institutional Environment and Public Officials' Performance in Guyana - Gokcekus, Omer; Manning, Nick; Mukherjee, Ranjana; Nallari, Raj (Washington, DC: World Bank, 2013)
The report presents the findings of a survey of public officials in Guyana, whose views were sought in a wide range of civil service issues - from personnel management, to rewards, and disciplinary actions, and, from budget environment to corruption. Answers were used to test some prior assertions about the public sector in the country, and, it is the respondents' belief that public sector jobs are attractive, though public employees are not fully prepared for their jobs through education, and training, nor is recruitment always based on merit. However, officials find policies consistent, but implement policies even if in disagreement with policy directions. Furthermore, decision-making is characterized by poor communication, and low employee participation. Nonetheless, officials surveyed showed insight about which reforms might enhance organizational performance, and, based on data analysis, quantification of how public officials assess the organizations' institutional environment, and performance was possible. Survey data demonstrated how widely varied the institutional environments of such organizations are, and, provided evidence that performance does depend upon institutional environment. The report prioritizes interventions according to the potential payoffs in different performance areas, suggesting performance monitoring is likely to be associated with significant positive change in performance.